Effects of Rain and Snow on the Air Quality Index, PM2.5 Levels, and Dry Deposition Flux of PCDD/Fs - Xueying Tian; Kangping Cui; Hwey-Lin Sheu; Yen-Kung Hsieh; Fanxuan Yu (Aerosol and Air Quality Research)
Abstract The effects of eighteen precipitation (rain and snow) events in both Jinan and Qingdao cities in Shandong Province, China, on the air quality and dry deposition flux in PCDD/Fs were investigated. A total of fifteen precipitation events were positive for AQI reductions. In these events, the AQI ranged between 29 and 195 and averaged 79, and the PM2.5 concentration ranged between 10 and 146 µg m−3 and averaged 39 µg m−3. A comparison of the average of the fifteen events during and after the precipitation, respectively, with that before the precipitation, showed AQI reduction fractions of 23% and 32%, respectively, while those for the PM2.5 concentration were 27% and 42%, respectively; the PCDD/F dry deposition ranged between 145.7 and 1152 pg WHO2005-TEQ m−2 day−1 and averaged 476.7 pg WHO2005-TEQ m−2 day−1. A comparison of the above events after the precipitation showed that the reduction in the fraction of the PCDD/F dry deposition flux averaged 35%. However, the other three precipitation events demonstrated an elevation in the AQI, where the AQI ranged between 24 and 147 and averaged 91, and the PM2.5 concentration ranged between 4 and 112 µg m−3 and averaged 42 µg m−3. A comparison of the values during and after the precipitation, respectively with those before the precipitation, revealed increased AQI fractions of –18% and 28%, respectively, while those for the PM2.5 concentration were 16% and 51%, respectively. In the three AQI elevation events, the PCDD/F dry deposition flux ranged between 191.3 and 946.2 pg WHO2005-TEQ m−2 day−1 and averaged 473.0 pg WHO2005-TEQ m−2 day−1. A comparison of the period after the precipitation with that before the precipitation showed that the increase in the fraction of the PCDD dry deposition flux averaged 20%. The above results revealed that, in general, rain and snow did improve the air quality in the areas of interest. This was due to the fact that the particulates or dissolved gaseous pollutants were scavenged out of the air and carried the aerosols down to the ground. However, in some events, after rainy or snowy days, increases in the source emissions and reductions in the atmospheric vertical convection did result in an elevation in the AQI, PM2.5 concentrations, and PCDD/F dry deposition in the ambient air. The results of this study provided useful information contributing to air quality management.